2016
DOI: 10.1007/s11106-016-9759-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical Boriding of Fe–5% Cr Alloy

Abstract: Boriding of the Fe-5% Cr alloy in amorphous boron powder with KBF 4 as an activator at 850-950°C and reaction times of 3600-28800 sec results in the formation of two boride layers at the interface between the reagents. The outer layer bordering boron consists of the FeB phase, while the inner one adjacent to the alloy base consists of the Fe 2 B phase. The average chromium content of the FeB layer is 4.2 wt.% (2.7 at.%) and of the Fe 2 B layer is 4.5 wt.% (3.5 at.%). The formation of boride layers is sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(10 reference statements)
0
7
0
1
Order By: Relevance
“…The vacuum device employed for boriding solid samples, details of the boriding procedure and investigational techniques used to characterize initial samples and boride layers formed on their surface have been described elsewhere [36,[47][48][49].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vacuum device employed for boriding solid samples, details of the boriding procedure and investigational techniques used to characterize initial samples and boride layers formed on their surface have been described elsewhere [36,[47][48][49].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Comparison of angles 2θ and spacing d of experimental X-ray patterns obtained with the literature data for iron and chromium borides [50][51][52][53][54][55] indicated that in the case of 5-15% Cr alloys and a 13% Cr steel the outer boride layer bordering the boriding agent is a solid solution based on the FeB chemical compound, Table 1 for a Fe-5% Cr alloy as an example [48,49]. It is the first type of their microstructure, which is usually observed with steels [1][2][3][4][5][6][7][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Phase Identity and Chemical Composition Of Boride Layersmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu kapsamda çelik için en önemli alaşım elementlerinden olan kromun borlama üzerine yalın etkisinin belirlenmesi için saf demir içerisine atomik olarak %5, 10, 15, 25 ve 30 oranlarında krom ilave edilerek Fe-Cr ikili alaşımları borlanmıştır [12]- [15]. Yapılan bu çalışmalarda Fe-Cr içerisindeki krom miktarındaki artışa bağlı olarak borür tabaka kalınlığının düştüğü, malzeme yüzeyinde oluşan borür tabakanın dış kısmı FeB fazından, iç kısmı ise Fe2B fazından oluştuğu ve buna ek olarak borür tabakası içerisinde ve kaplama-altlık ara yüzeyinde (Fe,Cr)B yapısında iğnemsi yapıların varlığı raporlanmıştır [12]- [14]. Bu çalışmada ise literatürde rapor edilmeyen atomik olarak eşit miktarda Fe ve Cr içeren Fe-Cr ikili alaşımı sentetik olarak üretilmiş, farklı sıcaklılarda aynı sürede yapılan kutu borlama tekniği ile kaplanarak karakterize edilmiş ve bu alaşımın borlama davranışı ortaya çıkarılmıştır.…”
Section: Introductionunclassified